Prioritization of sub-watersheds (third order) of the Sekmai river basin, Manipur, India - Karung Boboy Kom; Moirangthem Okendro; Ram Awadh Singh Kushwaha (National Geographical Journal of India, 2023)
Quantitative analysis of selected morphometric parameters under the GIS (Geographic Information System) spectrum of ASTER DEM with 30m resolution offers an attempt to prioritize third-order sub-watersheds of the Sekmai river basin. The outcome of this attempt divulges the susceptibility to flood, soil erosion, high runoff, and peak flow. River Sekmai is a sixth-order basin covering an area of about 380.32 km2. For a detailed morphometric analysis of linear, areal, and relief aspects seventy-eight third-order sub-watersheds are delineated. The main tributaries of the Sekmai River are LamlangLok, Maha River, Tisha River, and TimitLok. The result obtained from prioritization based on fifteen selected morphometric parameters reveals that sub-watersheds belonging to the first and second priority groups require immediate attention.